Chemical analysis of a basaltic weathering profile near Exeter, New South Wales, Australia - Menozzi, Davide; Dosseto, Anthony; Kinsley, Leslie P J (Supplement to: Menozzi, D et al. (2016): Assessing the effect of sequential extraction on the uranium-series isotopic composition of a basaltic weathering profile. Chemical Geology, 446, 126-137, https://doi.org/10.1016/j.chemgeo.2016.05.031, 2017)
Soil sustainability implies maintaining the balance between soil erosion and production. While it is known how to assess soil erosion, only recently we have been able to estimate rates of soil and saprolite (namely regolith) production using uranium-series isotopes. This method assesses the time elapsed since rock-forming minerals start fractionating the U-series isotopes. In this study, we assess a sample pre-treatment protocol that has the potential to improve the method used to estimate regolith production rates. We propose that removal (or partial removal) of secondary phases precipitated from solution during pedogenesis (solution-derived phases) and organic matter from regolith may improve the accuracy of this method. This is tested using sequential extraction followed by etching as sample pre-treatment. Here, we assess their effect on the U-series isotopic composition of regolith and infer whether they minimize the presence of solution-derived phases and organic matter. We applied sequential extraction and etching to a basaltic weathering profile (bedrock, saprolite and soil) and compared the U-series isotopic composition before and after treatment. We also measured major elements concentrations and assessed mineralogy. The bedrock was in secular equilibrium and sequential extraction resulted in unchanged (234U/238U) activity ratios, while increased (230Th/238U). In contrast, etching resulted in increased (234U/238U) and (230Th/238U) activity ratios, which is attributed to the removal of primary minerals. Relative to the untreated bedrock, the untreated saprolite showed no changes in U and Th concentrations, and activity ratios. We hypothesise that during the conversion of bedrock into saprolite U and Th budgets are unaffected. Moreover, major element and mineralogical analyses suggest that during this process rock-forming minerals are converted into secondary phases (clays). We hypothesise that during this conversion the U-series isotopes are not fractionated; therefore, the removal of these secondary phases is not necessary. Relative to the saprolite, the soil showed gains of U and Th, (234U/238U) > 1 and (230Th/238U) < 1. This could result from precipitation of solution-derived phases from soil-pore water and/or nuclide adsorption onto organic matter. These phases were removed by sequential extraction, which resulted in a residue with (234U/238U) < 1 and (230Th/238U) > 1. To minimize the presence of solution-derived phases and organic matter in basaltic weathering profiles we suggest that only soil samples should undergo sequential extraction, because only these are significantly affected by solution-derived phases and organic matter. Additionally, our experiments show the existence of fractionation processes that are often overlooked in U-series isotopic studies, i.e. implantation of 234U and 230Th recoiled from U-rich mineral (i.e. glass) into adjacent, U-poor phases (e.g. pyroxene and feldspar).